Big issues for small feet: developmental, biomechanical and clinical narratives on children’s footwear - Stewart C. Morrison; Carina Price; Juliet McClymont; Chris Nester (Journal of Foot and Ankle Research, 2018)
Abstract The effects of footwear on the development of children’s feet has been debated for many years and recent work from the developmental and biomechanical literature has challenged long-held views about footwear and the impact on foot development. This narrative review draws upon existing studies from developmental, biomechanical and clinical literature to explore the effects of footwear on the development of the foot. The emerging findings from this support the need for progress in [children’s] footwear science and advance understanding of the interaction between the foot and shoe. Ensuring clear and credible messages inform practice requires a progressive evidence base but this remains big issue in children’s footwear research.